TABOO LANGUAGE WITHIN TERNATE SOCIETY: A STUDY ON ITS FORMATION AND REFERENCE - Masayu Gay; Pipit A Susanti (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
This study aims at describing a formation, reference, and background of taboo language within the society of Ternate. This study employed qualitative design research. To obtain the data, this study employed observation, interview, and questionnaire. The results of this study demonstrate that (1) taboo language occur within society of Ternate are in the form of root word, derivative word, word repetition, phrase, and clause; (2) taboo language also occur in the form of synonym, particularly Ternate Local Language (BDT) and Ternate Malayan Langauge (BMT). The tendency of the individual in using swearing words is not based on acquired language, except, the individual aims at generating a certain expression based on theemotion. (3) It confirms that there are several swearing words predominantly utilized within the youth, the adult, and elderly; (4) It also confirms that the taboo language is directed to other people and the speaker her or himself. (5) Predominantly, the speaker refers to animal, plant, and human body’s part to taboo; (6) It confirms that there is a code-mixing between Ternate Local Language (BDT) and Ternate Malayan Language (BMT) as well as Indonesian Language(BI) and Ternate Malayan Language (BMT); (7) It further argues that taboo language is common to close friends or relatives or both speaker and hearer have the same age. On the other hand, it is considered as rude if the speaker and hearer have no social relationship or both have a different age. To sum up, taboo language is commonly employed by both speaker and hearer with the same age and possess close relationship.